Inventing Metaphors to Understand the Genre of Poetry - Phyllis Whitin (Journal of the Assembly for Expanded Perspectives on Learning, 2000)
To make personally meaningful connections with poetry as a genre, students in the author's seventh grade classes generated original metaphors to describe the essence of poetry.
Keywords: Poetry; poetry immersion; poetry metaphors; teaching poetry to elementary students